EKONOMI RUMAH TANGGA PETANI KOPI DI DESA PURWOREJO TIMUR KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - Friyantiarno Lasabuda; Juliana R. Mandei; Jenny Baroleh; Jean F.J. Timban (Universitas Sam Ratulangi, 2015)
ABSTRACT Friyantiarno Lasabuda, 080314034, Household Economic of Coffee Farmer in East Purworejo Modayag Distric East Bolaang Mongondow Regency under the guidance of Juliana Mandei as chairman, Jenny Baroleh and Jean Timban as members. This research aims to know how the characteristics of coffee farmer in East Purworejo Modayag Distric East Bolaang Mongondow Regency and how the revenue scheme and expenditure of the coffee farmer in this village. This research wasconducted in East Purworejo Modayag Distric East Bolaang Mongondow Regency. The data used in this study is primary data and secondary data, the primary data obtained from direct interview to 30 respondents of coffee farmer in east purworejo village and the secondary data obtained from related agency. Data are analyzed descriptively and presented in tabular form. The results showed that the income of coffee farmers in East Purworejo revenue comes from three sources, which is: coffee farming, farm income other than coffee, and income outside of farming, while household farmers expenditure is divided into three, which is food consumption expenditure, consumption expenditure non-food production and production investment and education. Coffee as the main agricultural commodity in this village with a large production costs are not capable of providing significant advantages over the life of farmers so that farmers seek other alternatives to cover household needs From this research, farmers in the East Purworejo to meet the needs of households consisting of consumption of food, non-food and investment. To cover the needs of farmers in this village not only rely on coffee farming as a main source of income but rather cultivate other crops and professions outside of farming in order to be able to cover the needs of farm households. Keywords : household economic, revenue and expenditure